Rilke contra Wagner. Rilke’s early concept of Music and the Convergence of the Arts around 1900 (Studia theodisca, 2011)
This article examines Rainer Maria Rilke’s fundamental distinction between the essence of music and poetry, concentrating on his earliest encounters with music around 1900 and their impact on his poetics. It places Rilke’s concept of music into the cultural context of the romantic experience and reception of music and the other arts in Germany at the turn of the century. Rilke’s early understanding is ultimately negative, deviating from the popularly held belief in fin de siècle Europe that all the arts are not just compatible but also in essence identical. For Rilke there can be neither a Wagnerian Gesamtkunswerk nor a greater underlying principle around which the arts could be united, despite his enthusiastic integration of the visual arts into his poetics.